METAPHYSICS MATTERS: METAPHYSICS AND SOTERIOLOGY IN JEROME STONE'S AND DONALD CROSBY'S VARIETIES OF RELIGIOUS NATURALISM. Issue 2 (June 2014) - Ruper, Stefani
Abstract Religious naturalism is distinct from supernatural religion largely because of metaphysical minimalism. Certain varieties of religious naturalism are more minimalist than others, however, and some even eschew metaphysics altogether. But is anything lost in that process? To determine metaphysics' degree of relevance to religious function, I compare the soteriology of the "ontologically reticent" Minimalist Vision of Jerome Stone to that of the ontologically rich Religion of Nature of Donald Crosby. I demonstrate that for these varieties of religious naturalism: (1) metaphysics influences soteriology; (2) metaphysical minimalism limits soteriological potential; and (3) metaphysics enhances soteriological potential. These conclusions lead me to assert the relevance of metaphysics to religious function, specifically for these varieties of religious naturalism, as well as to urge investigation into religious experience and quality as they may relate to metaphysics.